Application of internet and information technology in recruitment of safe blood donors. - Jalalian, Mehrdad M.; Abd Latiff, Latiffah; Syed Hassan, Syed Tajuddin; Hanachi, Parichehr; Othman, Mohamed Baharudin (Asian Network for Scientific Information, 2008)
The present study focuses on the role of information technology in blood safety policies. In order to reach to higher levels of blood safety we have to put our maximum force in the recruitment of safe blood donors via public education. Innovative use of mass media in recruitment of blood donors especially the youth and those of higher education level and disseminating the basic information about blood donation can be our success key. There is an urgent need to find new ways of recruiting blood donors rather than traditional methods of donor education. Effectiveness of internet based educational intervention in other disciplines of health has already been proven; however, few researches exist concerning internet application for online recruitment of safe blood donors. Finally, internet users' population and blood donors are similar in many aspects of their socio-demographic determinants and it is reasonable to deduce that online education and dissemination of knowledge of safe blood donation can be considered an efficient modus of recruitment of voluntary non-remunerated blood donors.